Comparative Analysis of Periapical Healing and Periodontal Health in Endodontically Treated Teeth with Different Obturation Techniques - Mayur Kahate; Rakhi Rajendran; Urvashi A. Shetty; Sufia Parveen; Ashtha Arya; Hanadi A. Alwafi (Journal of Pharmacy and Bioallied Sciences)
Background: The goals of endodontic therapy are to eradicate infection and encourage periapical tissue repair. The treatment’s outcome may be greatly impacted by the obturation method used. Materials and Methods: Ninety patients with comparable periapical lesions were grouped into three groups of 30 each for this randomized controlled experiment. Group C got single-cone obturation, Group B warm vertical compaction, and Group A cold lateral compaction. Assessments, both radiographic and clinical, were carried out at baseline, three months, and six months after therapy. The periapical index (PAI) was used to measure periapical healing, while bleeding on probing (BOP), clinical attachment level (CAL), and probing depth (PD) were used to measure periodontal health. Results: Group A had a mean PAI decrease of 3.1 ± 0.5, Group B 3.4 ± 0.4, and Group C 2.8 ± 0.6 during the 6-month follow-up. Group B had the biggest drop in probing depth (1.5 ± 0.3 mm), with Group A coming in second (1.3 ± 0.4 mm) and Group C third (1.0 ± 0.5 mm). In comparison to Group A (1.7 ± 0.3 mm) and Group C (1.5 ± 0.4 mm), Group B’s clinical attachment level improved the greatest (2.0 ± 0.4 mm). Group B (10%) had the lowest bleeding on probing ratings, followed by Group A (15%) and Group C (20%). Conclusion: When compared to cold lateral compaction and single-cone obturation, warm vertical compaction produced better outcomes for periapical healing and periodontal health. These results imply that obturation method is a major factor in the overall effectiveness of endodontic therapy.